A INFLUÊNCIA DA ARGAMASSA NO DESEMPENHO ACÚSTICO DE PAREDES DE VEDAÇÃO COM BLOCOS CERÂMICOS - Stradiotto, Júlia; Nunes, Maria Fernanda de Oliveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The NBR 15575 publication generated the need to understand the performance of systems and materials employed in construction. For this article a system that is widely used in Brazil was chosen with the purpose of analyzing and quantifying the acoustic performance of masonry ceramic blocks with different plaster combinations. Starting from previously conducted airborne sound insulation laboratory tests, results of three non-loadbearing wall systems were analyzed in a total of 11 compositions. The results showed that walls plastered on both sides can present up to 8dB increases in the Rw of the analyzed samples. Furthermore, we compared results of walls with filled and unfilled vertical joints and compared the results with the mass law projection.